Pengaruh Senam Otak terhadap Peningkatan Fungsi Kognitif - Inosensia Amtonis; Ulfa Husnul Fata (Journal of Ners and Midwifery, 2014)
The decline of cognitive function is a process of mental decline that include attention, language, memory, orientation capability, calculation and reasoning. Cognitive function changed significantly along the trajectories of the aging process. The function of Brain gym is important to improve brain function decline of the cognitive function in the elderly. The way of brain gym is to make a balance between the left and right brain functions. The purpose of this study was to determine the effect of brain gym to the enhancement of cognitive function in elderly at UPT PSLU Blitar. Method: The research design was one group pre-post test design on December 2-21 Juli 2014. The sampel of the research was 18 elderly at UPT PSLU Blitar, it was chosen using purposive sampling. The data analysis used Wilcoxon Signed Rank test. Result: The results showed that the elderly cognitive decline before doing the brain gym were 9 people (50%) in the category of severe, and after doing the brain gym the result were increased in the category of normal. There was significant effect in the catogories of cognitive function with p value 0.00. Discussion: It was suggested for nurses that brain gym had an effect to the improvement of cognitive function to elderly.